To Practice or Not to Practice: Perspectives of Traditional Birth Attendants and Local Communities in The Ga-West Municipality on the New Reproductive and Child Health (Rch) Policy in Ghana - Darko, M.L. (University of Ghana, 2015)
Maternal health remains a major issue in Ghana. Policies and programmes to address this phenomenon have been varied. The current policy by the Ministry of Health calls for skilled birth attendance for all and barring traditional birth attendants (TBAs) from conducting deliveries especially in communities with health facilities. No comprehensive studies have assessed the likely impact and response to the new maternal health policy in Ghana. The aim of this thesis therefore is to ascertain the views of local community members and TBAs on the new health policy. A total of 27 interviews were held with key stakeholders drawn from eight communities in the Ga-West Municipality of the Greater Accra Region in Ghana. The results reveal that community members, TBAs and rural health workers are generally unaware of any policy directive on the activities of TBAs. Community members were of the opinion that, barring TBAs from conducting deliveries will have serious implications for maternal health outcomes. It also came to light that the policy has come about because of the TBAs’ inability to handle complications and the delays parturient experience under TBAs which predispose them to maternal deaths. Maternal health policies in Ghana need to take into consideration the socio-cultural setting of the people for its implementation to be effective. Policy formulation and implementation must involve all stake holders concerned.
Thesis (MPhil) - University of Ghana, 2015